Testing the Rule of the Earliest Due Date (EDD) in Achieving the Priority of Delivery: A Case Study in the Directorate of Printing Press for the Iraqi Media Network - Amer Abdul Latif Kazem; Bilal Ahmed Hasan (Journal of Techniques)
On-time delivery is a key metric for evaluating the delivery performance of orders and the efficiency of an organization's supply chain. The main reasons behind the late delivery of orders is the lack of real-time data-driven insights, planning, monitoring and operational efficiency. Therefore, the study aims to apply the Earliest Due Date rule, which is one of the sequencing rules for the purpose of achieving the priority of delivery for requests at the study site, as well as evaluating the performance of delivery of requests on time according to the rule of the closest due date, and comparing it with the performance of the rule used in the study site, as The optimal sequence of a group of works leads to its delivery on time. The case study approach was adopted, as a number of completed works were selected as a sample to implement the study in the Directorate of Presses of the Iraqi Media Network. The study found that there is no prior planning for scheduling work in the publications production line, and delays in completing work lead to accumulation of work, delay in delivery and increase in costs. And the optimal sequence was found in the completion of the five work orders, through the sequence achieved in each of the rule of the nearest due date (EDD) and the rule of the critical ratio (CR), in light of which the delay time was addressed, and all work (requests) were delivered according to their specified time. As soon as possible, and the lack of direct coordination between the production department and the printing and correction departments to prepare a detailed scheduling, it also contributes to the completion of work orders for many external parties, and the exposure of the materials used in printing the publication to damage, due to its accumulation and waiting for processing on the machines, which leads to an increase Costs, delay in completing work, and the closest accrual rule has priority in completing work and achieving on-time delivery. The results of the relationship and impact analysis showed a strong inverse relationship between the on-time delivery measure and both the total completion time measure, and the average early completion time. The on-time delivery scale is directly related to determining the priority of completing work for the purpose of achieving certain goals, such as achieving the priority of delivery. The study reached a set of results, the most important of which was the great superiority of the results achieved by the proposed succession rules in finding the optimal sequence, as the closest due date rule (EDD) and the (CR) rule achieved preference in completing and delivering the works according to the specified time, and the speed in their delivery, compared to the results achieved when completing work orders on the basis of first-come-first-served (FCFS) used in the production line, as it did not have an effective role in improving delivery performance according to the specified time and speed of delivery.